Primary Fixation Feature Design Does Not Influence Total Ankle Tibial Component Stability When Implanted with Press-Fit in High Density Bone - Joshua E. Johnson PhD; Gabriel A. Clarke MS; Cesar de Cesar Netto MD, PhD; Donald D. Anderson PhD (Foot & Ankle Orthopaedics)
Category: Ankle; Basic Sciences/Biologics Introduction/Purpose: Initial implant stability is important for successful outcome after uncemented total ankle replacement (TAR) and long-term survival of the implant through adequate osseointegration. Implant-bone micromotion is one factor used to evaluate implant stability, as small micromotions are known to facilitate bony ingrowth, whereas excessive micromotions result in deleterious fibrous tissue ingrowth. Commercial TAR tibial components are available in a wide range of fixation feature shape and size designs to aid primary fixation stability. However, influence of patient-specific bone density on TAR performance is poorly understood, especially for implants that rely upon interference fit for stable primary fixation. The goal of this project was to computationally evaluate1 how bone density influences implant-bone interface micromotions in three TAR tibial component designs: resurfacing, stemmed, and modular-stem. Methods: Finite element analysis was conducted in four TAR patients with varying bone densities as judged from anonymized CT scan data. Global bone density T-scores were approximated from average CT Hounsfield unit (HU) values over a distal tibia region of interest.2-5 Tibia geometries were obtained from CT scan data. Generalized representations of three tibial implants were evaluated – a bone-sparing resurfacing implant (Paragon 28), a cortex-sparing, anterior approach monoblock stemmed implant, and a distal-reaming, modular-stem implant. Implant positioning and interference fit (100 µm) were set according to surgical guidelines (Fig. 1A). Tibia bone was assigned material properties6 based on local HU values to model permanent deformation during simulated implantation. Implants were assigned titanium alloy properties. Press-fit was modeled first, followed by a series of loadings from the stance phase of gait.7 Micromotions were computed as difference in displacement between implant-bone closest nodal pairs. Peak and average micromotions were compared throughout stance. Results: T-scores calculated for Patient’s 1, 2, 3, and 4 were 1.62, 2.10, -0.85, and -2.03, respectively (Fig. 1B). In general, patients with high-density bone (T-score>0) had lower micromotions than patients with low-density bone (T-score< 0; Fig. 1C and 1D). Implant fixation feature design had less of an influence on micromotion in patients with high-density bone (Patients 1 and 2), with peak micromotions ranging from 2 to 23 µm (3.1±1.3 µm). While higher micromotions were observed in patients with low-density bone (Patients 3 and 4), micromotions were lowest with the modular-stem implant (29 and 32 µm peak values for Patient’s 3 and 4, respectively) compared to the monoblock stemmed implant (47 and 52 µm peak values) and the resurfacing implant (108 and 67 µm peak values). Conclusion: We investigated influence of bone density on implant-bone micromotion with realistic primary press-fit fixation and physiologic loading. Local bone density plays an important role in primary fixation stability of TAR tibial components. Micromotion was low with bone compaction in high-density bone, regardless of implant design. However, both stemmed devices demonstrated lower micromotion in less-dense bone given clinical trade-offs of more tibial bone removal, and in the case of the modular stem, disruption to the calcaneus and talus. Understanding how local bone density, implant fixation and design features together contribute to implant stability in TAR is necessary to improve implant performance.